An Environmental Health Study of Medical Waste in Nablus Hospitals - Yousef Sadek Hasan Khaleel Al-Qaroot (My University, 2001)
Field investigations of four hospitals medical wastes in Nablus City were carried out in 1998 and 1999. The management of medical waste in Palestine was not given the proper attention. Still there are lacks of legislation and defined policy regarding this issue. The entire medical waste generated is dumped within general waste. Medical waste generated at four hospitals (Ratidia, AI-Watani, Al—lttehad, and Al-lnjili) in the city of Nablus, were weighted twice over 11 days during March-June 1999, and during November —December 1999, and generation rates, volume and density of medical waste were calculated. Hepatitis B serology tests were also carried out in 62 waste care workers from the study hospitals during December 1999. This study shows the average daily quantities and generation rates of four general, governmental and none-governmental, hospitals were mentioned. Also the social and health conditions of the waste care workers in these hospitals were mentioned too. Generation rates (kg/bed/day) were 0.67 in Ratidaia, 0.83 in AI—Watani, 0.76 in AI—lttihad, and 0.69 in Al—lnjili hospitals. While the generation rates (kg/in-patient day) were 0.96 in Rahdia, 1.34 in Al-Watani, 1.18 in AI-lttihad, and 1.37 in Al-lnjili hospitals. Results of serological tests for Hepatitis B virus, for 61 waste care workers (20 in Ratidia, 12 in Al-Watani, 11 in AI-lnjili, and 19 in AI-Ittehad hospitals), were negative, while the results were positive for one case (one worker from Rahdia hospital), so that the prevalence of Hepatitis B for waste care workers was 1.6%.

Field investigations of four hospitals medical wastes in Nablus City were carried out in 1998 and 1999. The management of medical waste in Palestine was not given the proper attention. Still there are lacks of legislation and defined policy regarding this issue. The entire medical waste generated is dumped within general waste. Medical waste generated at four hospitals (Ratidia, AI-Watani, Al—lttehad, and Al-lnjili) in the city of Nablus, were weighted twice over 11 days during March-June 1999, and during November —December 1999, and generation rates, volume and density of medical waste were calculated. Hepatitis B serology tests were also carried out in 62 waste care workers from the study hospitals during December 1999. This study shows the average daily quantities and generation rates of four general, governmental and none-governmental, hospitals were mentioned. Also the social and health conditions of the waste care workers in these hospitals were mentioned too. Generation rates (kg/bed/day) were 0.67 in Ratidaia, 0.83 in AI—Watani, 0.76 in AI—lttihad, and 0.69 in Al—lnjili hospitals. While the generation rates (kg/in-patient day) were 0.96 in Rahdia, 1.34 in Al-Watani, 1.18 in AI-lttihad, and 1.37 in Al-lnjili hospitals. Results of serological tests for Hepatitis B virus, for 61 waste care workers (20 in Ratidia, 12 in Al-Watani, 11 in AI-lnjili, and 19 in AI-Ittehad hospitals), were negative, while the results were positive for one case (one worker from Rahdia hospital), so that the prevalence of Hepatitis B for waste care workers was 1.6%.
An Environmental Health Study of Medical Waste in Nablus Hospitals